2011
DOI: 10.1111/j.1440-1681.2011.05477.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of the nefopam–paracetamol combination in rodent models of antinociception

Abstract: 1. The aim of the present study was to explore the concept of multimodal anaesthesia using a combination of two non-opioid analgesics, namely nefopam, a centrally acting non-opioid that inhibits monoamine reuptake, and paracetamol, an inhibitor of central cyclo-oxygenases. The antinociceptive characteristics of the combination were evaluated using four different animal models of pain. 2. In the mouse writhing test, antinociceptive properties were observed with ED50 values of 1.5 ± 0.2 and 120.9 ± 14.8 mg/kg fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
(55 reference statements)
2
16
0
1
Order By: Relevance
“…The median effective dose (ED50) of the two drug's coadministration was significantly lowered compared with that of nefopam alone, and it was suggested that the nefopam and ketoprofen interaction may be additive, with a possible tendency toward synergy (3). Another study also illustrated the enhanced antinociceptive properties of combined administration of nefopam and acetaminophen in a writhing test, in which a 36.3±5.5 mg/kg ED50 value was observed on coadministration compared with 1.5±0.2 and 120.9±14.8 mg/kg for nefopam and acetaminophen, respectively (25). Meanwhile, Miranda et al (36) confirmed a synergistic interaction between paracetamol and tramadol on their coadministration via i.p.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The median effective dose (ED50) of the two drug's coadministration was significantly lowered compared with that of nefopam alone, and it was suggested that the nefopam and ketoprofen interaction may be additive, with a possible tendency toward synergy (3). Another study also illustrated the enhanced antinociceptive properties of combined administration of nefopam and acetaminophen in a writhing test, in which a 36.3±5.5 mg/kg ED50 value was observed on coadministration compared with 1.5±0.2 and 120.9±14.8 mg/kg for nefopam and acetaminophen, respectively (25). Meanwhile, Miranda et al (36) confirmed a synergistic interaction between paracetamol and tramadol on their coadministration via i.p.…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated that nefopam has synergistic analgesic effects in humans and rodent animals when administered concomitantly with nonsteroidal anti-inflammatory drugs (3,(23)(24)(25). A previous clinical trial indicated that a combination of nefopam and ketoprofen produced effective analgesia with synergistic interaction in humans (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that DA played a critical role in nefopam analgesia as indicated by the observation that rats with selective loss of DA neurons, have a marked reduction in nefopam-induced analgesia. In a marked contrast, the lesion of the serotonergic or noradrenergic systems induced by 5,7-duhydroxytryptamine (5,7-DHT) or DSP4, respectively, failed to affect nefopam-induced analgesia in rats (Esposito et al, 1986;Girard et al, 2006;Girard et al, 2011). The potential interest of TRIs in the relief of pain has been corroborated by a recent publication characterizing the antinociceptive effects of the TRI bicifadine in acute, www.intechopen.com persistent and chronic models of pain (Basile et al, 2007).…”
Section: Pain Relief By Tris An Example Of Symptom Of Depressionmentioning
confidence: 99%